STUDI KOMPARATIF TENTANG HUKUM KEWARISAN ANAK TEMUAN PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Zamzami, Izzuka; M. Chamim (Irtifaq, 2020)
This article examines the differences in the inheritance of children found according to Islamic law and positive law. This research uses descriptive qualitative method and the type of research used is literature review using comparative analysis. The results of this study can be concluded that adoption of the findings in Islamic law and positive law is allowed. The rule of law for the inheritance of children found in Islamic law is through wills with an amount of 1/3 of the assets or more. Meanwhile, in positive law, namely through a will grant. In contrast to Staatsblad 1917 Number 129 which states that adopted children have the same position as heirs.Keywords: Children Findings, Inheritance Law, Comparative Law.